2018
DOI: 10.3892/etm.2018.6410
|View full text |Cite
|
Sign up to set email alerts
|

Reduced hepcidin level features osteoporosis

Abstract: Osteoporosis (OP) is a common serious skeletal disorder marked by increased risk of bone fracture due to fragility. OP has been taken to be a disease linked with abnormal calcium metabolism that alone is obviously insufficient to explain the development of OP. Iron overload has been associated with the development of OP and increasing studies have suggested the association. However, direct evidence for this has not been clinically established. To this end, using the Roche biochemical autoanalyzer, we detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Iron overload (an elevated ferritin level) is a risk factor for progressive bone loss in healthy postmenopausal women and middle-aged men and a risk factor for radiological vertebral fracture in postmenopausal women 13 . Liu et al compared serum hepcidin levels in 40 patients with osteoporosis and 40 healthy controls 14 . They identified lower serum hepcidin levels and higher iron levels in patients with osteoporosis compared to healthy controls, and the serum hepcidin level was negatively related to the serum iron level 14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Iron overload (an elevated ferritin level) is a risk factor for progressive bone loss in healthy postmenopausal women and middle-aged men and a risk factor for radiological vertebral fracture in postmenopausal women 13 . Liu et al compared serum hepcidin levels in 40 patients with osteoporosis and 40 healthy controls 14 . They identified lower serum hepcidin levels and higher iron levels in patients with osteoporosis compared to healthy controls, and the serum hepcidin level was negatively related to the serum iron level 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al compared serum hepcidin levels in 40 patients with osteoporosis and 40 healthy controls 14 . They identified lower serum hepcidin levels and higher iron levels in patients with osteoporosis compared to healthy controls, and the serum hepcidin level was negatively related to the serum iron level 14 . In this study, the serum hepcidin level was positively related to serum iron and ferritin levels, and serum iron levels were positively related to BMD, in contrast to the studies outlined above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased estrogen levels in postmenopausal women lead not only to the imbalance of bone metabolism but also to increased LPI, which becomes a dual risk factor for PMOP. Current clinical evidence showed that PMOP patients tend to have iron overload symptoms including decreased hepcidin levels (Liu et al, 2018) and high serum ferritin levels (Cheng et al, 2017), which in turn exacerbate bone loss. Epimedii Folium is an effective Chinese herb used for thousands of years to treat orthopedic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Hepcidin knockout mice had a higher serum ferritin level and higher iron in the liver than controls and showed low bone mass and changes in bone microarchitecture [99]. Liu et al compared serum hepcidin levels in 40 patients with OP and 40 healthy controls demonstrating lower serum hepcidin levels and higher iron levels in patients with OP and that the serum hepcidin level was negatively related to the serum iron level [100]. In contrast, Sato et al demonstrated that the serum hepcidin level was positively related to serum iron and ferritin levels, and serum iron levels were positively related to BMD [99].…”
Section: Iron Metabolism and Osteoporosismentioning
confidence: 99%